Determinan Akses Sumber Air Minum Layak di Provinsi Bengkulu Tahun 2021 - Monica Putri; Aisyah Fitri Yuniasih (Politeknik Statistika STIS, 2022)
Safe and proper drinking water is an important element in realizing a healthy life. During the 2017-2021 period, Bengkulu Province became the province with the lowest average percentage of access to safe drinking water in Indonesia. In 2021, the percentage of access to safe drinking water sources in Bengkulu Province is still below the national level, which is 67,39 percent. This figure still cannot reach the RPJMN target to achieve access to safe drinking water of 100 percent. The purpose of this study is to provide a general picture and analyze the influencing variables and trends in access to adequate drinking water sources in Bengkulu Province in 2021with the multilevel binary logistic regression analysis method. The results of this study indicate that variables at the household level, namely regional classification, sanitation facilities, KRT education and poverty status have a significant effect on access to adequate drinking water sources. Then the variable at the regional level, namely GRDP per capita also has a significant effect on access to decent drinking water sources.